Understanding Engineering Undergraduates’ Technical Oral Presentation: Challenges and Perspectives - Abdullah Adnan, Mohamed; Adelina, Asmawi (Universiti Malaysia Pahang, 2018)
This paper reports the findings of an evaluation study on technical oral presentation and its potential application in English language courses for engineering undergraduates setting. The main aim is to delineate difficulties and challenges faced by engineering undergraduates in learning Technical Oral Presentation (TOP) skills in an English proficiency course. The participants were 310 engineering undergraduates who enrolled in the English for Technical Communication (ETC) course and nine instructors. Various difficulties and challenges faced by the engineering undergraduates to learn the TOP skills were identified and input from instructors were also examined. Suggestions to address the challenges faced by the students were highlighted with the view to preparing them for their future engineering workplace communication